PERSPEKTIF PENJOR GALUNGAN OLEH MASYARAKAT HINDU DI KOTA PALU - Dani, Ni Luh Sari; Ratini, Ni Ketut; Suarnada, I Gede (STAH Dharma Sentana Sulawesi Tengah, 2024)
Hindus carry out part of religious ceremonies, one of which is making a Galungan penjor which is something sacred. Based on the researcher's observations and interviews with several informants, there are still Hindu communities in Palu City who do not put up penjor when celebrating the Galungan holiday. Research problem formulation: (1) What is the Hindu community's perspective on the function of the penjor? (2) What are the obstacles for Hindu communities not installing penjor? (3) What efforts have been made by the Hindu community to maintain the installation of the penjor? Based on the research results, it was obtained: (1) The Hindu community's perspective on the function of penjor a) as an expression of gratitude, b) welfare and prosperity, c) humility, d) the embodiment of God's palace, e) victory over Adharma (2) The obstacles are not Installing Penjor a) internal obstacles, namely busyness (limited time in making), limited materials and lack of understanding the true meaning of penjor, b) external obstacles, namely, lack of family support, economic factors, focus of celebration venues not only in Palu and the neighborhood where you live which is heterogeneous, (3) Efforts are made to maintain the installation of penjor, a) providing freedom in creativity in making it, b) promoting it on social media, c) socializing the importance of the meaning of penjor.